Analgesic effect of premedication with meperidine in patients undergoing colonoscopy without sedation. Issue 1 (23rd April 2014) - Tsai, Ming‐Chang; Chen, Tan‐Hsia; Lai, Hsin‐Wu; Chen, Tzy‐Yen; Chang, Ming‐Huei; Lin, Chun‐Che
Summary: Background: Colonoscopy is a standard and useful examination in the diagnosis of colorectal diseases; however, it usually causes pain to patients. Some patients receive narcotic drugs, e.g., meperidine, for pain relief if a colonoscopy is carried out without sedation. Whether the administration of such analgesic drugs to patients without sedation facilitates the performance of the colonoscopy or reduces pain remains to be elucidated. The aim of this study was to evaluate the analgesic effect of meperidine as premedication for patients undergoing a colonoscopy without sedation. Patients and Methods: A total of 217 patients (109 men, 108 women) undergoing a diagnostic colonoscopy without sedation were analyzed prospectively. The procedures were carried out by three experienced endoscopists in a medical center. The patients could opt to receive analgesic drugs, with 25 mg of meperidine being given intramuscularly prior to the procedure if requested by either the doctor or patient. The colonoscopic examination was performed by one person using the short‐axis method. Questionnaires to evaluate abdominal pain during or after colonoscopy without sedation were collected and analyzed for patients who used meperidine as premedication (Group A) and for those who did not receive meperidine (Group B). Abdominal pain was evaluated using a visual analog scale from 0 to 10. The cecal intubation rate, total insertion time, and the patient's willingness to receive another colonoscopy in the future if needed were also analyzed. Results: In both groups, the cecal intubation rate was more than 99% with no significant difference between groups. The mean ± standard deviation insertion time was 7.14 ± 5.45 minutes in Group A and 6.24 ± 4.24 minutes in Group B ( p = 0.309). The visual analog pain score was 3.54 ± 3.13 in Group A and 2.46 ± 2.75 in Group B ( p = 0.009). After adjusting for age and sex, the pain score was 3.51 ± 3.21 in Group A ( p = 0.055). Multivariate analysis showed that female sex and the individual endoscopist performing the colonoscopy were associated with abdominal pain during the examination. Conclusion: In our study, premedication with meperidine or no premedication was not associated with a reduction in abdominal pain during colonoscopy without sedation. The insertion time and cecal intubation rate showed no difference between patients with or without additional analgesic drugs prior to the procedure. However, as self‐selection bias could not be ruled out, further randomized, placebo‐controlled trials are needed to confirm our findings.